Pengaruh Kemajuan Teknologi, Efikasi Diri, Konformitas Teman Sebaya dan Tuntutan Orang Tua Terhadap Perilaku Menyontek Siswa pada Mata Pelajaran Ekonomi di SMAN 5 Padang - Gumanti, Dessyta; Rahmania, Meri; Sari, Wardani Purnama; Wati, Wati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the influence of technological advances, self-efficacy, peer conformity, and parental demands on student cheating behaviour in Economics at SMAN 5 Padang Gunung Talang. The study used a quantitative approach with an associative descriptive design. The study population consisted of 271 students, with a sample of 134 students selected using proportional random sampling based on Isaac and Michael's formula at a 5% error rate. Data were collected using a 1–5 Likert scale questionnaire that had been tested for validity and reliability. All instruments were declared valid and reliable. Data analysis was performed through prerequisite tests and multiple linear regression using SPSS. The results showed that technological advances and peer conformity had a positive and significant effect on student cheating behaviour, while self-efficacy and parental demands had a negative and significant effect. Simultaneously, all four variables had a significant effect on cheating behaviour. These findings indicate that cheating behaviour is influenced by individual and social factors, thus requiring the joint role of schools and parents in strengthening students' self-efficacy and academic ethics.